THE DEVELOPMENT OF FOOD SECURITY EDUCATION PROGRAMS IN ISLAMIC BOARDING SCHOOLS THROUGH CURRICULUM INTEGRATION AND EXPERIENTIAL PRACTICE - Subagiya, Bahrum; Hidayat, Muhammad Faishal; Alwahid, Muhamad Azhar; Rifa, Fauzan Ahmad; Al Khathier, Muhammad Rayyan (LPPM Univ. Ibn Khaldun Bogor, 2025)
Food security remains a critical challenge in Indonesia, where population growth, land conversion, and environmental degradation threaten sustainable food systems. Islamic boarding schools (pesantren), as influential educational and community-based institutions, hold significant potential to contribute to food security through integrated education and practice. By embedding food security concepts into curricula and daily routines, pesantren can cultivate a holistic model that unites faith, knowledge, and sustainability. This study emphasizes the role of santri in developing practical competencies through hydroponics, aquaponics, biopore infiltration systems, organic waste utilization, and sustainable cultivation. These practices not only ensure the availability of nutritious food for students but also foster ecological awareness, technical skills, and entrepreneurial capacity. The methodology includes the development of structured learning modules, hands-on training, teacher capacity building, and institutional integration, supported by monitoring and evaluation mechanisms to ensure sustainability. A notable example is Pesantren Tahfiz Al-Qur’an Ibnu Jauzi, Dramaga, Bogor, which demonstrates the potential to combine religious education with innovative food security initiatives. In the long term, pesantren-based programs strengthen institutional self-sufficiency, reduce dependency on external supplies, and empower surrounding communities, positioning pesantren as strategic actors in advancing national food sovereignty and sustainable development.